KARAKTERISTIK EDIBLE FILM DARI BERBAGAI JENIS UMBI-UMBIAN DENGAN PENAMBAHAN GLISEROL: STUDI KEPUSTAKAAN - Madu, Wa Ode Al Wahyuni Madu Al Wahyuni; Wahyuni, Sri; Susilowati, Prima Endang (Jurnal Sains dan Teknologi Pangan, 2022)
ABSTRACTThis review aimed to see the effect of adding glycerol on the characteristics of edible films produced from various types of tubers. The addition of glycerol is done to increase the elasticity properties so that the bond can increase the molecular distance from the polymer. The glycerol compound is effective in increasing the plastic properties of the film because it has a small molecular weight so that it can reduce the intermolecular forces along the polymer chain which causes the starch film to be flexible and easy to bend. The results of the review show that the addition of glycerol has been proven to improve the characteristics of the edible film of various types of tubers. The physical and chemical properties improvements of edible films include thickness, tensile strength, percent elongation, and water content so that the edible films produced can be applied as packaging materials for food products.Keywords: edible film, tubers, glycerolABSTRAKReview ini bertujuan untuk melihat pengaruh penambahan gliserol terhadap karakteristik edible film yang dihasilkan dari berbagai jenis umbi-umbian. Penambahan gliserol dilakukan untuk untuk meningkatkan sifat elastisitas sehingga ikatan dapat menaikan jarak molekul dari polimer. Senyawa gliserol efektif dalam menaikkan sifat plastik film karena memiliki berat molekul yang kecil sehingga mampu menurunkan gaya intermolekul sepanjang rantai polimernya yang menyebabkan film dari pati akan lentur dan mudah dibengkokkan. Hasil review menunjukkan bahwa penambahan gliserol terbukti dapat memperbaiki karakteristik edible film dari berbagai jenis umbi-umbian. Perbaikan yang dimaksud adalah sifat fisik dan kimia edible film yang meliputi ketebalan, kuat tarik, persen pemanjangan dan kadar air sehingga edible film yang dihasilkan mampu diaplikasikan sebagai bahan pengemas pada produk pangan.Kata kunci:edible film, umbi-umbian, gliserol